Moldova Financial Sector Assessment Program : Bank Crisis Resolution - International Monetary Fund (Washington, DC, 2015)
The FSAP mission to Moldova included an assessment of the financial crisis resolution framework, focusing on bank resolution arrangements. The FSAP did not include an assessment of crisis resolution arrangements in respect of insurance, Financial Market Infrastructure (FMI) or other types of financial institutions. However, many of the findings and recommendations made in this report in relation to bank crisis resolution are also likely to be pertinent to other parts of the financial sector. Accordingly, the authorities are encouraged to draw on this Technical Note to assist them in reviewing the crisis resolution framework applicable to insurance, FMI and other categories of financial institution. The assessment was undertaken having regard to the principles set out in the Financial Stability Board’s (FSB’s) key attributes of effective resolution regimes for financial institutions (key attributes). In undertaking this assessment, the mission reviewed relevant legislation applicable to bank crisis resolution, particularly the law on financial institutions and the Law on the National Bank of Moldova. It also reviewed the government decree establishing the NCFS and the MOU established for members of the NCFS.